Still connecting the dots: An investigation into infants' attentional bias to threat using an eye‐tracking task. (30th November 2021) - Sareen, Sinia; Doyle, Frances L.; Kemp, Lindsay J.; Northam, Jaimie C.; Morgan, Bronte G.; Kimonis, Eva R.; Richmond, Jenny L.; Le Pelley, Mike E.; Eapen, Valsamma; Frick, Paul J.; Hawes, David J.; Moul, Caroline; et al.
Abstract: An attentional bias toward threat has been theorized to be a normative aspect of infants' threat and safety learning, and an indicator of risk for internalizing psychopathology in older populations. To date, only four studies have examined this bias using the dot‐probe task in infancy and the findings are mixed. We extended the literature by examining patterns of attention to threat in a culturally and linguistically diverse sample of infants aged 5–11 months old ( N  = 151) using all measures previously employed in the infant dot‐probe literature. Given that an attentional bias toward threat is associated with higher risk of developing anxiety disorders later in life, we also examined how negative affect—an early correlate of later anxiety disorders—is related to attentional bias toward threat in infancy. This study was the first to use a consistent measure of negative affect across the whole sample. An eye‐tracking dot‐probe task was used to examine attentional bias toward threat (i.e., angry faces) relative to positive (i.e., happy faces) stimuli. Results showed that an attention bias to threat was not characteristic of infants at this age, and negative affect did not moderate the putative relationship between attention and emotional faces (angry, happy). These findings therefore suggest that attention biases to socio‐emotional threat may not have emerged by 11 months old.